Penentuan Penerima Bantuan Sembako Dengan Sistem Pendukung Keputusan Di Yayasan Vihara Dharmaloka Pekanbaru Menggunakan Metode Analytical Hierarcy Process (AHP) - Aldi Aldi; Hadion Wijoyo (Mahesa Research Institute, 2023)
Vihara Dharma Loka Pekanbaru Foundation conducts a program, namely the distribution of basic food assistance to underprivileged families before chinese new year annually. This program is to help people who are Buddhists lived in Pekanbaru which is carried out at the Vihara Dharma Loka Pekanbaru Foundation which is located at Jl. Dr. Leimena No. 41 Pekanbaru. There is no decision system in determining the recipients of basic food assistance so that the recipients of assistance are still not on target. The purpose of this research is to design a computerized decision support system to determine the recipients of basic food assistance using the method Analytical Hierarchy Process (AHP). Supported by expert choice application for the implementation process, the calculation resulted for each criterion have some weights, electric bill 0.433, income below 2 million with a weight of 0.396 and children under working age with a weight of 0.172.